FORMULATION AND EVALUATION OF ANTIAGING PHYTOSOMAL GEL - Mariam Joshua, Julie; Anilkumar, Athira; Cu, Verjina; T Vasudevan, Deepa; A Surendran, Saritha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the present study was to prepare and evaluate antiaging phytosomal gel. Method: For this purpose, tender coconut water, Aloe vera extract, grape seed extract, vitamin E, and jojoba oil were taken. The cytokinins present in coconut water show astounding effects in preventing premature aging. A. vera contains Vitamin E and C and phenol compounds which contribute to aging. Grape seed extract contains polyphenols mainly in the form of flavonoids which are highly potent antioxidants. It also possessed an antiaging vitamin known as oligomeric proanthocyanidins which prevented premature aging. Vitamin E was chosen because of its antioxidant properties. Jojoba oil was chosen because it had good moisturizing properties and it was similar to human skin oil, sebum. Conventional dosage forms such as creams and gels were prepared using these ingredients, but they showed less antiaging effect. Therefore, phytosome was prepared by binding herbal extracts to phosphatidylcholine (acts as a carrier and nourishes the skin). They had a phospholipid molecular structure which included a water-soluble head and two fat-soluble tails, and due to this dual solubility, it was better absorbed and so it was used for the treatment of skin disorders, antiaging, and skin carcinomas. Result: Nine different formulations of the antiaging cream, gel, and phytosomal gel were prepared. Physicochemical parameters such as pH, viscosity, homogeneity, spreadability, and extrudability were determined. In vitro antioxidant studies were performed for the prepared antiaging cream, gel, and phytosomal gel. Among the three different formulations, phytosomal gel was chosen to be the best formulation to treat wrinkles and blemishes on the skin. When compared to the conventional dosage forms such as creams and gels, the phytosomal gel could release the herbal ingredients and showed better penetration into the skin. From the nine different formulations, F2 containing both tender coconut water and A. vera extract was chosen as the optimized formula. Optimization was done on the basis of in vitro antioxidant studies and physicochemical parameters. F2 acts as a potent free radical scavenger and inhibits oxidation by free radicals. 2,2-diphenylpicrylhydrazyl free radical scavenging assay was chosen as the best method in screening the antioxidant activity of the herbal extracts. The IC50 value of the prepared antiaging cream, gel, and phytosomal gel was found to be 70.5 μg/ml, 65.0 μg/ml, and 47.0 μg/ml, respectively. The lower the IC50 value, the highest the antioxidant activity. Thus, the antiaging phytosomal gel proved to show the highest antioxidant activity. The stability of the optimized formulation was carried out at two different temperatures, 30°C ± 2°C and 4°C ± 2°C, and the formulation was found to be stable at the end of 45 days. Conclusion: From the present study, it can be concluded that the prepared antiaging phytosomal gel was safe, convenient, and efficient carrier to deliver the herbal extracts. It also showed better penetration into the skin. Hence, the desired antiaging property was obtained. It is because of this reason, it is used in skin care cosmetics, mainly for antiaging treatment.